Resisting reform? water profits and democracy - Urs, Kshithij; Whittell, Richard (Delhi London SAGE, 2009)
'Resisting Reform?' looks at the attempts that have been made to 'reform' Bangalore's water supply, situating them in their global and national context and that of the city's broader development. The authors argue that treating water as a commodity is a dangerous principle for any water service, public or private
Title from title screen (viewed October 20, 2023)
Includes bibliographical references
Specialized
Description based on print version record
Keywords: Privatization -- India -- Bangalore; Water-supply -- India -- Bangalore